An air mass‐derived cool season climatology of synoptically forced Appalachian cold‐air damming. (5th July 2017) - Ellis, Andrew W.; Marston, Michael L.; Nelson, Daniel A.
ABSTRACT: An air mass approach was used to identify episodes of cool season cold‐air damming (CAD) within the central Appalachian Mountains region of the eastern United States. Daily air mass type data were used to identify days on which moist polar (MP) air was regionally evident east of the mountains, while non‐MP air was in place at nearby stations west of the mountains. Over a 35‐year study period, 219 CAD days were identified (>6 per year) with the annual frequency exhibiting no trend but suggesting that El Niño (La Niña) coincides with a greater (lesser) frequency of CAD days in winter (December–February). Synoptic atmospheric composites reveal west‐to‐east migration of a parent anticyclone to a classic position along the border of the northeastern United States and southeastern Canada. This coincides with a pattern of amplifying and slowly eastward‐moving 500 hPa height anomalies characterized by positive (negative) values over eastern (western) North America that are signalled a few days in advance by the index representing the Pacific‐North American teleconnection pattern. Confinement of the CAD below the 850 hPa level is evident in the synoptic wind field, while the composite vertical profile of the atmosphere within the CAD environment further depicts the shallow nature of the surface‐based cool, moist air. Northeasterly winds at the surface veer to southeasterly within a few hundred metres above the surface, and then southwesterly at less than one km above the surface, at the 850 hPa level. The air mass approach to CAD identification appears to successfully identify regional occurrences of synoptically forced CAD, although it likely does not detect local and/or diabatically forced CAD. Abstract : An air mass approach is used to identify occurrences of synoptically‐forced cold‐air damming (CAD) within the central Appalachian Mountains region of the eastern United States. Results indicate that El Niño (La Niña) coincides with a greater (lesser) frequency of winter CAD days. CAD days coincide with amplifying and eastward‐moving 500 hPa height anomalies characterized by positive (negative) values over eastern (western) North America that are signaled a few days in advance by the index representing the Pacific‐North American teleconnection pattern.